The complexity of climate reconstructions using the coexistence approach on Qinghai–Tibetan Plateau - Zhi-Yong Zhang; Dong-Mei Cheng; Cheng-Sen Li; Wan Hu; Xuan-Huai Zhan; Hong-Li Ji (Journal of Palaeogeography, 2019)
Abstract Quantifying the palaeoclimates of Qinghai–Tibetan Plateau is vital for understanding the uplift history of plateau and the evolution of Asian monsoon since Cenozoic. Recently, the Coexistence Approach (CA) has been employed to reconstruct the palaeoelevation and palaeoclimate of the plateau by several studies. However, the application of CA in mountainous areas and the realism of climate reconstructions via this method are seldom discussed, although the complexity of reconstructions is speculated. Here we reevaluated the realism of climate reconstruction using the CA with modern pollen samples from the Qinghai–Tibetan Plateau, and try to explore the possible factors influencing the precipitation and temperature reconstructions by CA. We suggest that the long-distance transport pollen as a result of the Asian summer monsoon potentially significantly affects the reconstructions both for precipitation and temperature. The precipitation complexly interacting with snowmelt and permafrost thaw leads to the discrepancy between the reconstructed precipitation and the real value. The response temperature for blossoming of dwarfed plants on the plateau is mostly likely higher than the air temperature (usually measured at 1.5 m above ground) due to energy flux or morphological adaptation of inflorescences during the growing season, causing the distortion of temperature reconstructions. Precipitation reconstruction is notoriously difficult as the establishers of CA have already suggested, but reconstructing the low temperatures may be even more challenging on Qinghai–Tibetan Plateau. Though all of the explorations in current paper are in a qualitative way, it offers an inspiration of how appropriately interpret the disagreements between CA results and the observations, and of how to obtain a reasonable reconstruction of palaeoclimate of the plateau.